(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
Level control of liquid in a tank or any similar container is widely used in applications such as chemical and oil industrial processes. Control the level at desired value is very important. This paper studies the performance of P, PI, and PID controllers in controlling the level of a liquid. Mass balance is used to find mathematical model of water tank level. Ziegler-Nichol (Z-N) and Cohen-Coon (C-C) tuning methods are used to evaluate parameters of the controllers. The error indices such as Integral Absolute Error (IAE) and Integral Squared Error (ISE) are used to compare between performances of the controllers. MATLAB is used to test the control system performance and compare the results with real values. Both simulation and experimental results show that liquid level system can be controlled effectively by using Z-N tuning method. The result shows that the PI controller gives better performance in comparison with P and PID controller.